Geoarchaeological record of human activity during the Neoholocene in the south-eastern Iłża Foothills (Central Poland)): https://doi.org/10.26485/AGL/2018/107/9 - Szeliga, Marcin; Dobrowolski, Radosław; Chodorowski, Jacek; Pidek, Irena Agnieszka; Mroczek, Przemysław (Acta Geographica Lodziensia, 2018)
The article presents the results of geoarchaeological research carried out within and around two multicultural archaeological sites in Tominy and Zawada (south-eastern Iłża Foothills), in the immediate vicinity of the northern edge of the loess cover of the Sandomierz Upland. The main objective of the research was to comprehensively reconstruct human settlement and economic activity in the study area in the last ca. 5,000 years, along with identifying its conditions, both at the chronologicalcultural and the environmental level. The results allowed a determination of the course and scale of local cultural phenomena and related settlement processes between the late Neolithic and modern times. On the basis of traces of exploitation and transformation of the natural environment, an attempt was made to determine the nature and extent of local anthropopressure in the Neoholocene.